Children's eating attitudes test (ChEAT): reliability and validation in German children and adolescents based on clinical data - Lena Nonnast; Laura Maria Derks; Natalie Deux; Martin Holtmann; Tanja Legenbauer (Eating and Weight Disorders)
Abstract Purpose The objective of this study is to assess the validity of the German version of the Children's Eating Attitudes Test (ChEAT), an internationally used tool for the detection of eating disorder (ED) symptoms, in a clinical sample. Methods The ChEAT self-report questionnaire, comprising 26 items, was employed to examine eating behaviors of a clinical sample of 342 adolescents (aged 12–18 years) undergoing inpatient treatment at a child and adolescent psychiatric clinic in Germany. The ChEAT was validated through an exploratory factor analysis (EFA), followed by a confirmatory factor analysis (CFA) and an examination of internal consistency. Subsequent analyses were conducted to identify differences associated with participant characteristics, including age, gender, body mass index (BMI), and diagnosis. Furthermore, additional eating behaviors, depression, and anxiety symptoms were documented via supplementary questionnaires and correlated to the ChEAT to evaluate the convergent and discriminant validity. Results The factorial validity of the ChEAT was confirmed through EFA and CFA, resulting in a five-factor structure with the following dimensions: 'Body and Weight Concern,' 'Dieting,' 'Social Pressure,' 'Purging and Binge Eating,' and 'Food Preoccupation'. The 24-item model showed high internal consistency and demonstrated an acceptable fit to the data. Convergent and discriminant validity of the ChEAT was supported by significant correlations with other self-report questionnaires. Higher ChEAT average scores were observed in females and those with a history of eating or depressive disorders, whereas age or BMI showed no correlation. Conclusion The data demonstrate that the German version of the ChEAT appears to be a reliable and valid instrument for identifying ED symptoms in clinical samples. However, further studies are necessary to evaluate the factor structure and validity. Level of evidence V, cross-sectional, descriptive study.